Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5539/jsd.v4n1p211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Resource Factors on Perceived Environmental Performance: an Empirical Analysis of a Sample of ISO 14001 EMS Companies in Malaysia

Abstract: Increasing employee motivation for environmental endeavors continues to be poorly understood. The literature suggests that management commitment, employee empowerment, feedback and review, and rewards may be significant predictors of environmental performance and hence successful environmental management system (EMS) implementation. This paper aims to ascertain the relationships between the aforementioned human resource factors with perceived environmental performance using a sample of middle and lower level e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 61 publications
2
30
0
4
Order By: Relevance
“…ISO 14001 is also used as a strategy for improving stakeholders' satisfaction in general; in particular, the external stakeholders, usually identified as the community, are the most affected in terms of satisfaction (Bansal and Hunter, ; Hubbard, ; Tuppura et al , ). Another important stakeholder positively affected in terms of satisfaction by ISO 14001 certification seems to be employees; various authors reported that environmental strategies positively affect employee satisfaction objectives (Sharma and Kodali, ; Hubbard, ; Kaur, ; Curkovic and Sroufe, ; Santos et al , ; Tarí et al , ). In fact, an EMS is often associated with an improvement in workplace health and safety conditions (Tinsley, ; Ahsen, ; Wiengarten et al , ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…ISO 14001 is also used as a strategy for improving stakeholders' satisfaction in general; in particular, the external stakeholders, usually identified as the community, are the most affected in terms of satisfaction (Bansal and Hunter, ; Hubbard, ; Tuppura et al , ). Another important stakeholder positively affected in terms of satisfaction by ISO 14001 certification seems to be employees; various authors reported that environmental strategies positively affect employee satisfaction objectives (Sharma and Kodali, ; Hubbard, ; Kaur, ; Curkovic and Sroufe, ; Santos et al , ; Tarí et al , ). In fact, an EMS is often associated with an improvement in workplace health and safety conditions (Tinsley, ; Ahsen, ; Wiengarten et al , ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…The survey items for management commitment (item number 1 to 9), employee empowerment (item number 10 to 17), feedback and review (item number 18 to 25), and rewards (item number 26 to 33) can be found in Kaur's (2011) study on the relationship between HR factors and perceived environmental performance. The scales are measured using a five-point Likert scale (1=strongly disagree, 5 = strongly agree).…”
Section: Surveymentioning
confidence: 99%
“…The aim of this paper is to extend previous research by proposing and testing an integrative research model which links several HR factors to employee attitudes. The HR factors identified include management commitment, empowerment, feedback and review, and rewards (Govindarajulu & Daily, 2004, p. 365;Kaur, 2011). In essence employee attitude reflects job satisfaction and the individual's commitment to the organization (Landy, et al, 1993 as cited by Karia & Asaari 2006, p. 33).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations